Nigeria and World War II : colonialism, empire, and global conflict - Korieh, Chima Jacob 1962- (Cambridge University Press, 2020)
Fighting for the world : imperialism, wartime policy, and colonial subjects -- For King and country : colonial subjects, and wartime intellectualism -- The home front : colonial subjects and the burden of empire -- Voices of protest : austerity, regulations, and social protest -- The Second World War and its aftermath -- Conclusion.